1979
DOI: 10.1111/j.1748-5827.1979.tb07029.x
|View full text |Cite
|
Sign up to set email alerts
|

A new test for the diagnosis of exocrine pancreatic insufficiency in the dog

Abstract: A new approach to the diagnosis of exocrine pancreatic insufficiency in the dog has been evaluated. The synthetic peptide, N-benzoyl-L-tyrosyl-paminobenzoic acid, administered orally, is specifically cleaved by pancreatic chymotrypsin to release p-aminobenzoic acid (PABA) which is subsequently absorbed and excreted in the urine. The assay of plasma PABA or the estimation of urinary excretion over a 6-hour period was found to give a clear differentiation between two small groups of healthy dogs and animals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…An accurate diagnosis can be made by the assay of pancreatic enzymes in the lumen of the proximal small intestine. In order to avoid duodenal intubation this has been achieved in viva for chymotrypsin by the oral administration of a synthetic peptide (Freudiger & Bigler, 1977;Batt, Bush & Peters, 1979b). Small intestinal damage can also result in the malabsorption of many nutrients (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…An accurate diagnosis can be made by the assay of pancreatic enzymes in the lumen of the proximal small intestine. In order to avoid duodenal intubation this has been achieved in viva for chymotrypsin by the oral administration of a synthetic peptide (Freudiger & Bigler, 1977;Batt, Bush & Peters, 1979b). Small intestinal damage can also result in the malabsorption of many nutrients (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis was confirmed by the oral administration of N-benzoyl-L-tyrosyl-p-aminobenzoic acid, a substrate specific for chymotrypsin, and the subsequent estimation of plasma and urine p-aminobenzoic acid (PABA) (Batt et al, 1979b). The results (Table 1) show that at two hours normal animals achieve a plasma PABA concentration approximately 10 times greater than that of the animals with pancreatic insufficiency.…”
Section: Groups Of Animalsmentioning
confidence: 92%
“…The clinical details and results of the screening tests (Batt et al, 1979b) are shown in Table 1. The diagnosis was confirmed by the oral administration of N-benzoyl-L-tyrosyl-p-aminobenzoic acid, a substrate specific for chymotrypsin, and the subsequent estimation of plasma and urine p-aminobenzoic acid (PABA) (Batt et al, 1979b).…”
Section: Groups Of Animalsmentioning
confidence: 99%
“…Bacterial proteolytic activity may 0022-45 10/84/1200-0707%02.00 0 1984 BSAVA 707 add a further complication by falsely elevating the results in dogs with EPI. The oral N-benzoyl-L-tyrosyl-P-aminobenzoic acid test has helped to overcome these difficulties (Freudiger & Bigler, 1977;Strombeck, 1978;Batt, Bush & Peters, 1979;Rogers et al, 1980;Batt & Mann, 1981), however, practical constraints are likely to limit the widespread application of this procedure. As an alternative approach a radioimmunoassay has been developed for the accurate detection of EPI by the analysis of a single blood sample (Williams & Batt, 1983).…”
Section: Introductionmentioning
confidence: 99%